Analysis of consumers' self-congruity through halal fashion brand personality - Dini Salmiyah Ali; Athaya Kamila matanra (Journal of Halal Product and Research)
The halal industry in Indonesia is developing brilliantly, including in halal fashion. Behind the great potential and desire to become the mecca of world Muslim fashion, there is intense competition between fashion brands and consumers who tend to be critical in making their choices.  Facing this new reality, a company in this industry must ensure that it can maintain its existence in the long term by creating its product identity (brand personality) and understanding consumer behavior that tends to direct choices to brands they feel are close or suitable to itself, including PT Soka Cipta Niaga (SOKA) as a company that produced the first halal socks. The purpose of this study is to examine how the suitability of consumers' self-image through the personality of a halal fashion brand. This study uses a qualitative approach with descriptive research and data collection techniques conducted through in-depth interviews with Focus Group Discussions (FGD), observation, and documentation of SOKA consumers.  The results of the study show that there are only three dimensions of the personality of the halal brand that is most prominent from the SOKA brand, namely excitement, purity, and righteousness personality.  Among these three personalities, righteousness then becomes the only halal brand personality that is most congruence with the actual and ideal self-image of its consumers, which can help to show and satisfy their self-concept needs for religious obedience and adherence in using products that are considered relevant to sharia principles.